Applying SAVI Approach To Improve Exposition Writing Skills In 5th Grade Students of Penabur Christian Elementary School 6 - Merinda, Merinda; Zulela, Zulela; Marini, Arita (International Journal for Educational and Vocational Studies, 2019)
This study aims to improve exposition writing skills of the 5th grade students through the application of the SAVI approach (Somatic, Auditory, Visual and Intellectual) in learning. This study is an action research carried out at SDK 6 Penabur North Jakarta. The research subjects were 5th grade students, amounting to 35 students. The implementation of the study was divided into two cycles, each cycle carried out three and four meetings. Data analysis techniques were carried out with qualitative descriptive techniques. The success of this study was seen from two criteria, namely the observation sheet applying the SAVI approach and increasing the results of exposition writing skills. The results of the study obtained are the application of the SAVI approach to make students actively move and search for their own information, students are increasingly active in group learning, creation of written and product made by students and able to find their own knowledge and skills. The increase in the results of exposition writing skills is also seen in the initial cycle and is increasing in cycle 2. This can be seen from the initial percentage of students who have not completed the task of exposition writing skills by 68%, then the percentage results in the first cycle are 45.7% and in the end of the second cycle students who obtained incomplete results were only 25.7%. Overall at the end of the second cycle all aspects and criteria for exposition writing experienced a significant increase.